1962
DOI: 10.1021/bi00912a018
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Pancreatic Procarboxypeptidase B. II. Mechanism of Activation*

Abstract: The present report extends a preceding investigation of the isolation, characterization, and activation of bovine pancreatic procarboxypeptidase B (Wintersberger et al., 1962). The amino acid composition of the zymogen and of crystalline carboxypeptidase B derived from it is given in detail. The amino terminal residue of carboxypeptidase B has been identified as threonine. The initial stage of activation of procarboxypeptidase B has been examined, and evidence has been obtained that the appearance of activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

1965
1965
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…Analysis of the inhibitor profile, pH optimum and amino acid composition of the purified insulin-secretorygranule carboxypeptidase indicated that it is distinct from carboxypeptidase N (Plummer & Hurwitz, 1978), lysosomal carboxypeptidase B (Ninjoor et al, 1974;Lones et al, 1983), exocrine (pro)carboxypeptidase B (Folk et al, 1960;Cox et al, 1962) and urinary carboxypeptidase (kininase) (Skidgel et al, 1984). However, its properties do resemble those of the enzyme variously termed 'enkephalin convertase', 'carboxypeptidase E' and carboxypeptidase H (EC 3.4.17.10), which B A 0 0.05 k 0 J.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the inhibitor profile, pH optimum and amino acid composition of the purified insulin-secretorygranule carboxypeptidase indicated that it is distinct from carboxypeptidase N (Plummer & Hurwitz, 1978), lysosomal carboxypeptidase B (Ninjoor et al, 1974;Lones et al, 1983), exocrine (pro)carboxypeptidase B (Folk et al, 1960;Cox et al, 1962) and urinary carboxypeptidase (kininase) (Skidgel et al, 1984). However, its properties do resemble those of the enzyme variously termed 'enkephalin convertase', 'carboxypeptidase E' and carboxypeptidase H (EC 3.4.17.10), which B A 0 0.05 k 0 J.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentrations were determined from the absorbance at 280 mg, El2¿, = 21 (Cox et al, 1962). Enzymatic Activities.…”
Section: Methodsmentioning
confidence: 99%
“…It was therefore of interest to ascertain whether the zinc-binding site of bovine carboxypeptidase B shared some of the features of that of carboxypeptidase A. The presence of seven cysteic acid residues in the acid hydrolysate of the performic acid-oxidized enzyme (Cox et al, 1962) lends added interest to such an investigation, since, potentially, more than one cysteinyl residue could participate in the binding of the metal atom. The present experimental findings show, however, that six of the seven cysteic acid residues occur as disulfide-bonded cystines; this leaves only one cysteinyl residue as a potential ligand for zinc, and this is, in fact, its function in the native enzyme.…”
mentioning
confidence: 99%
“…CPBs from porcine and bovine pancreases have been isolated and well characterized (Folk et al, 1960;Folk et al, 1962;Wolff et al, 1962;Cox et al, 1962;Wintersberger et al 1962;Schmid & Herriott, 1976;Clauser et al, 1988;Edge et al, 1998;Ventura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%